الأحاديث الواردة في كتاب " خزينة الأسرار جليلة الزكار" للأمام محمد حقي النازلي ( ت: 1031 ه \ 1884م) : دراسة وتخريج - Wahyu Hidayat Bin Abdullah
The treatise entitled Khazinah al-Asrar Jalilah al-Azkar is one of the most circulated hadith texts amongst the Muslims especially in the Malay World. It is written by Muhammad Haqqi al-Nazilli (d. 1884CE); a scholar who lived in the 19th century. The book contains a large number of hadith from the Prophet SAW dealing mainly with the subject relating to the virtues of actions (fada 'il al-a 'mal) and the virtues of certain chapters and verses of the Quran. This study aims to analyze the hadith method employed by al-Nazilli in his book, and ascertain the origins and status of the hadiths mentioned therein in terms of reliability. The study employs the historical and textual analysis methods in reconstructing the life and works of the author as well as understanding his method in hadith appraisal. At the same time, the method of ascertaining the origins and status of the hadith is based on the principles used by the hadith scholars on the matter. The findings of the study highlight the prominence of al-Nazilli as a great Muslim scholar in 19th century Mecca especially in the fields of hadith,fiqh and Sufism, and an author of a number of influential works. His method of hadith appraisal in his work Khazinah al-Asrar represents his attempt to harmonize between the methods of the hadith scholars and the Sufis. This study also identify the total of hadith in this book are 725, including 225 of it were authentic hadith, 227 were hadis dha'if, 153 were hadis mawdu', while the rest 112 of those hadith were in status are yet to be kown.